2009
DOI: 10.17221/132/2009-pse
|View full text |Cite
|
Sign up to set email alerts
|

Denaturing gradient gel electrophoresis as a fingerprinting method for the analysis of soil microbial communities

Abstract: In soil microbial ecology, the effects of environmental factors and their gradients, temporal changes or the response to specific experimental treatments of microbial communities can only be effectively analyzed using methods that address the structural differences among whole communities. Fingerprinting methods are the most appropriate technique for this task when multiple samples must be analyzed. Among the methods currently used to compare microbial communities based on nucleic acid sequences, the technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 61 publications
0
14
0
5
Order By: Relevance
“…However, it has been demonstrated that a reduced number of PCR cycles and mixing replicate reactions do reduce the risk of bias [39, 40], and this was therefore the approach adopted here to maximize the probability that any differences identified were not experimental artefacts.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that a reduced number of PCR cycles and mixing replicate reactions do reduce the risk of bias [39, 40], and this was therefore the approach adopted here to maximize the probability that any differences identified were not experimental artefacts.…”
Section: Discussionmentioning
confidence: 99%
“…ITS2 (5'-GCT GCG TTC TTC ATC GAT GC-3') and ITS4 (5'-TCC TCC GCT TAT TGA TAT GC-3') were used for reverse primers (Valášková and Baldrian, 2009). ITS1 region of fungal ribosomal DNA (rDNA) was amplified by nested PCR.…”
Section: Pcr Amplificationsmentioning
confidence: 99%
“…A nested PCR for the V3 region was performed on the 8F/1492R PCR products using the 341F-gc (5'-CGC CCG CCG CGC GCG GCG GGC GGG GCG GGG GCA CGG GGG GCC TAC GGG AGG CAG CAG-3') and 518R (5'-ATT ACC GCG GCT GCT GG-3') primers (Valášková and Baldrian, 2009). The PCR included a 4-min denaturation step at 94 °C followed by 35 thermal cycles of 1 min at 94 °C, 30 s at 52 °C, and 90 s at 72 °C, and a final extension at 72 °C for 10 min.…”
Section: Pcr Amplificationsmentioning
confidence: 99%
“…Microbial diversity was screened by Denaturing Gel Gradient Electrophoresis (DGGE). A semi-nested PCR was performed using primers with a GC-clamp (Muyzer et al, 1993); fungal and algal ITS rRNA was amplified from environmental DNA with primers ITS1F-GC/ITS2 (Gardes and Bruns, 1993; White et al, 1990), following the protocol reported in Selbmann et al (2017), while 341F-GC/518R primers (Muyzer et al, 1993) were utilized for 16S rRNA amplification (Valášková and Baldrian, 2009) (Table 2).…”
Section: Methodsmentioning
confidence: 99%